2015
DOI: 10.1021/acs.jafc.5b02914
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, Nutrition, and Health-Promoting Properties of Hericium erinaceus (Lion’s Mane) Mushroom Fruiting Bodies and Mycelia and Their Bioactive Compounds

Abstract: The culinary and medicinal mushroom Hericium erinaceus is widely consumed in Asian countries, but apparently not in the United States, for its nutritional and health benefits. To stimulate broader interest in the reported beneficial properties, this overview surveys and consolidates the widely scattered literature on the chemistry (isolation and structural characterization) of polysaccharides and secondary metabolites such as erinacines, hericerins, hericenones, resorcinols, steroids, mono- and diterpenes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
164
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(200 citation statements)
references
References 134 publications
(241 reference statements)
1
164
0
5
Order By: Relevance
“…Free radical accumulation is an essential factor contributing to cellular apoptosis, and numerous natural products have been shown to control intracellular free radical levels [24]. HE has also been reported to display strong antioxidant effects, which may be directly associated with its broad therapeutic benefits [16]. As a hub for Ca 2+ signaling, which is an effector of ATP, mitochondria are considered central to intracellular energy metabolism [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free radical accumulation is an essential factor contributing to cellular apoptosis, and numerous natural products have been shown to control intracellular free radical levels [24]. HE has also been reported to display strong antioxidant effects, which may be directly associated with its broad therapeutic benefits [16]. As a hub for Ca 2+ signaling, which is an effector of ATP, mitochondria are considered central to intracellular energy metabolism [25].…”
Section: Discussionmentioning
confidence: 99%
“…Hericium erinaceus , an edible and medicinal mushroom, displays various pharmacological activities in the prevention of dementia in conditions such as PD and AD [15]. H. erinaceus water extracts have been reported to show antitumor, antimutagenic, antioxidant, hypolipidemic, and immunomodulatory properties in cell and animal models [16]. Encouragingly, H. erinaceus displays neuroprotective properties, such as facilitating nerve growth factor (NGF) expression and secretion and regulating the differentiation and development of cholinergic neurons in in vitro and in vivo experiments [2].…”
Section: Introductionmentioning
confidence: 99%
“…are also known for their therapeutic potential especially in stimulation or synthesis of nerve growth factor (NGF) and several health-promoting principles including those used in treatment of dementia (e.g. metabolites of H. erinaceus: Kawagishi and Zhuang 2008, Ma et al 2010, Friedman 2015, Thongbai et al 2015. It is also known that H. erinaceus possess polysaccharide belonging to -glucan group showing potent antitumor activities (Seok et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…H. erinaceus can produce mycelia and biological metabolites, such as erinacines and hericenones, by liquid and solid-state fermentation without harmful effects [1, 2]. Either the H. erinaceus mycelium (erinacines A-I) or its fruit bodies (hericenones C-H) are the source of many bioactive extracts with valuable biological properties [3]. This study has identified that H. erinaceus has a number of therapeutic properties, such as antioxidant activity [1], hypolipidemic activity [4], hemagglutinating activity [5], antimicrobial activity [6], antiaging activity [7], and anticancer activity [8, 9].…”
Section: Introductionmentioning
confidence: 99%